2010
DOI: 10.1007/s00423-010-0612-7
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous laparoscopic assisted gastrostomy (PLAG)—a new technique for cases of pharyngoesophageal obstruction

Abstract: PLAG is a safe and easy procedure. It can well be used to provide enteral access for patients with pharyngoesophageal obstruction not suitable for endoscopic PEG placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Dormann et al [14] reported that long-term follow-up in patients with gastrostomy using this gastropexy kit revealed only 2.1% peristomal infection, and without any serious complications. Bolder et al [6] demonstrated that percutaneous laparoscopically assisted gastrostomy to provide enteral access for patients with pharyngoesophageal obstruction was not suitable for PEG placement. Our laparoscopic gastropexy method using two straight needles is an application of this kit for laparoscopic surgery, and this method is easy and safe even for surgeons with limited laparoscopic surgery experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dormann et al [14] reported that long-term follow-up in patients with gastrostomy using this gastropexy kit revealed only 2.1% peristomal infection, and without any serious complications. Bolder et al [6] demonstrated that percutaneous laparoscopically assisted gastrostomy to provide enteral access for patients with pharyngoesophageal obstruction was not suitable for PEG placement. Our laparoscopic gastropexy method using two straight needles is an application of this kit for laparoscopic surgery, and this method is easy and safe even for surgeons with limited laparoscopic surgery experience.…”
Section: Discussionmentioning
confidence: 99%
“…Several modified procedures of laparoscopic gastrostomy have been introduced [5,6,7,8,9,10]. These procedures do not always allow gastropexy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the various PEG techniques [2,3] at present have several limitations with regard to tube placement; this method is not always feasible or safe, e.g., in cases in which endoscopic passage is not possible because of an obstruction in the neck or esophageal stenosis, morbid obesity, ascites, or when the colon or liver overlay the stomach [4]. Surgery has been proven to be a reliable and safe method of gastrostomy and several modified procedures of laparoscopic gastrostomy have been introduced [4][5][6][7][8][9]. These procedures do not include a parietal gastropexy with a subsequent weak attachment to the abdominal wall.…”
mentioning
confidence: 98%